(6x+1)/(2x-1)=5

Simple and best practice solution for (6x+1)/(2x-1)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+1)/(2x-1)=5 equation:



(6x+1)/(2x-1)=5
We move all terms to the left:
(6x+1)/(2x-1)-(5)=0
Domain of the equation: (2x-1)!=0
We move all terms containing x to the left, all other terms to the right
2x!=1
x!=1/2
x!=1/2
x∈R
We multiply all the terms by the denominator
(6x+1)-5*(2x-1)=0
We multiply parentheses
(6x+1)-10x+5=0
We get rid of parentheses
6x-10x+1+5=0
We add all the numbers together, and all the variables
-4x+6=0
We move all terms containing x to the left, all other terms to the right
-4x=-6
x=-6/-4
x=1+1/2

See similar equations:

| (7+2x)/2=5 | | 4-3(p+2)=2(p-4) | | 5x+3x=5-2 | | x+88=121 | | k.12=-5k-3 | | -8x+2=28 | | (6x+1)/(2x-1)=9 | | 0.5(5-7x=8-1(4x+6) | | 4+3(w-9)=-12 | | P(x)=-6x-9 | | 5x+3x=2+5 | | 7x−9=4x | | 43+8p=p+21 | | 2x+45=87 | | 13+2a=3a-14+24 | | 14v+50=2(5v+29) | | 420(2r+10=) | | -w+66=2w | | 8x=x2+15 | | n4+5=17 | | y2-144=0 | | 4-3t=6t-8 | | 3x-9-3=2x+14 | | Y=6E-06x | | 18c–25=38 | | 4(n+5)=17 | | -5(x+2)+16=15-6x | | −5(x+2)+16=15−6x | | 2d−6=2 | | 3x+(4x+13)=125 | | 0.4(2x+1/2)=3(0.2+(-2))-4 | | 3x-10=2x+14 |

Equations solver categories